Strategies for Intercultural Communication in Multicultural Educational Environments - I Nyoman Tri Esaputra (Universitas Pendidikan Ganesha, 2024)
Intercultural communication in multicultural educational environments presents both challenges and opportunities for educators and students. Effective communication strategies are essential to fostering inclusive learning and minimizing misunderstandings arising from linguistic and cultural diversity. This study aims to explore intercultural communication strategies employed by educators in multicultural educational settings and analyze their effectiveness in promoting meaningful interactions. Using a qualitative research approach, data were collected through in-depth interviews, observations, and document analysis. Participants included educators and students from diverse cultural and linguistic backgrounds. Thematic analysis was conducted to identify patterns and strategies used in classroom communication. The findings reveal that educators implement various strategies, such as code-switching, contextualized teaching, and the use of visual aids, to bridge language and cultural differences. Additionally, the study highlights the role of empathy, cultural sensitivity, and active listening in enhancing communication effectiveness. The results indicate that the successful application of these strategies fosters inclusive learning environments, improves student engagement, and reduces cultural barriers. The study concludes that intercultural communication strategies play a critical role in shaping effective teaching and learning in multicultural settings. These findings have significant implications for teacher training programs, emphasizing the need for intercultural competence and adaptive communication techniques to support diverse student populations.